2021
DOI: 10.14744/semb.2021.58219
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte to Monocyte Ratio and C-Reactive Protein Combination as the Best Simple Predictor of Treatment Response in Cirrhotic Patients With Culture Negative Neutrocytic Ascites

Abstract: A scites is the most common complication and reason of the hospitalization in the cirrhotic patients. Almost 60% of patients with cirrhosis will develop ascites within 10 years after diagnosis of the disease. [1] Cirrhotic patients with ascites are generally prone to developing bacterial infection of ascitic fluid. The prevalence of spontaneous bac- Objectives:The aim of this study was to evaluate the most ideal inflammatory markers for treatment response and to determine a cutoff value that could predict resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Our study results are in agreement with Barutcu et al (13) who enrolled 50 patients with cirrhotic ascites who were divided into three groups: Group A: 20 patients with SBP diagnosed laboratoraly. Group B: 20 patients with criteria suggestive of SBP, but shows neutrophil count in ascitic fluid <250.…”
Section: Discussionsupporting
confidence: 93%
“…Our study results are in agreement with Barutcu et al (13) who enrolled 50 patients with cirrhotic ascites who were divided into three groups: Group A: 20 patients with SBP diagnosed laboratoraly. Group B: 20 patients with criteria suggestive of SBP, but shows neutrophil count in ascitic fluid <250.…”
Section: Discussionsupporting
confidence: 93%
“…A study demonstrated the use of LMR and C-reactive protein to monitor treatment response. In the study, after the study group received antibiotic treatment, C-reactive protein levels were significantly lower, and LMR was elevated [ 3 ]. We did not use these markers upon initial diagnosis and treatment of our patient’s care of CNNA.…”
Section: Discussionmentioning
confidence: 99%
“…There are two significant groups of infection regarding ascitic fluid: spontaneous bacterial peritonitis (SBP) and culture-negative neutrocytic ascites (CNNA). Diagnostic criteria for CNNA are an ascitic fluid polymorphonuclear leukocyte count >250/mm, an ascitic fluid culture negative for bacterial growth, no prior antibiotic therapy within 30 days, and no infectious source within the abdomen [ 3 - 5 ]. CNNA generally has a lower risk for mortality, which was demonstrated across multiple studies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 , 13 ] HE who develops CLF, on the other hand, presents with a wide variety of neurological symptoms, including mood swings, impaired sleep-wake cycles, changes in muscle tone, and severe cognitive deficits. [ 14 , 15 ] Just as in the presence of sepsis and inflammation, blood levels of inflammation mediators such as tumor necrosis factor-alpha, Interleukin (IL)-1β, and IL-6 have been found to increase in patients with HE. Moreover, the development of astrocyte swelling-brain edema by these mediators suggests the possibility of exacerbation in HE.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the development of astrocyte swelling-brain edema by these mediators suggests the possibility of exacerbation in HE. [ 14 , 15 ] Despite all the studies in the literature, it is suggested that these inflammatory factors other than ammonia, including infection, cytokines, and other blood and brain immune factors, play a potential role in the pathogenesis of HE, but the data on these factors are basic. [ 15 , 16 ]…”
Section: Discussionmentioning
confidence: 99%